Strategies for Increasing Protection Effectiveness in the Camplong Nature Park Area, Kupang Regency, East Nusa Tenggara Province - Wilfrido Ridwan Seu; Maria M. E. Purnama; Astin E Mau (Wana Lestari, 2020)
Camplong Nature Tourism Park (NTP) is one of the conservation areas in Kupang Regency, East Nusa Tenggara Province. The NTP Camplong area is partially designated as a Nature Tourism Park managed by the Natural Resources Conservation Agency East Nusa Tenggara (BBKSDA NTT) based on the Decree of the Minister of Forestry Number: SK.347 / MenhutII / 2010 with an area of ​​696.60 Ha. One of the management activities carried out in Camplong NTP is protection of forest areas. Protection efforts are faced with various threats, including being located near settlements and public roads, making them vulnerable to habitat destruction. Forest fires, illegal use of area resources and waste disposal are the main problems that threaten the existence of the NTP Camplong area. Based on the Management Effectiveness Tracking Tool (METT) assessment by BBKSDA NTT, the METT score was 69%, from the minimum value of 70%. This study aims to determine the effectiveness and strategies to increase the effectiveness of efforts to protect the Camplong Nature Park area. The research was conducted in July-August 2019 at NTP Camplong. Data collection was carried out by direct observation and in-depth interviews. From the research results, it is known that the management aspects in the form of planning, organizing, implementing, and monitoring carried out in NTP Camplong have generally been implemented even though they have not run optimally. This has an impact on the less than optimal protection efforts for the NTP Camplong area. Strategies for increasing the effectiveness of the management of the NTP Camplong area, namely: strengthening management management; increasing the implementation of area protection and security; coordination with government and legal institutions; as well as increasing community participation in area protection efforts.